The Influence of Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions on Donation Intention and Use Behavior of Kitabisa.com Among Generation Z - Yolanda Amelia; Aditya Sujarminto; Putu Bagus Tutuan Aris Kaya; Annisa Putri (Universitas Teknologi Yogyakarta, 2025)
This study aims to investigate the influence of Generation Z's donation interest in Bogor Regency in using the crowdfunding platform Kitabisa.com, employing the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The research method utilized in this study is a quantitative approach, specifically employing a questionnaire for data collection. Sampling was conducted using a purposive sampling method, yielding a total of 110 respondents. The analytical method employed in this research is multiple linear regression analysis using SPSS 25 software. This study examines the factors influencing donation intention and usage behavior on online donation platforms, specifically Kitabisa.com, among Generation Z. The findings indicate that performance expectancy, effort expectancy, and social influence contribute to donation intention, supporting SDG 1 (No Poverty) and SDG 10 (Reduced Inequalities). Additionally, facilitating conditions and donation intention influence usage behavior, aligning with SDG 17 (Partnerships for the Goals). These results highlight the role of Kitabisa.com in enabling donations and fostering a spirit of mutual assistance in the digital era. This study contributes to understanding Generation Z’s donation behavior and its relevance to achieving the Sustainable Development Goals (SDGs).